The return of Skeleton Man - Bruchac, Joseph, 1942- (HarperTrophy, 2008)
When Molly and her parents attend a conference at Mohonk Mountain House, Molly begins to fear that she is being watched by the very man who kidnapped and tried to kill them all the previous year.